2022
DOI: 10.1002/ijc.33990
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the telomerase reverse transcriptase promoter and PIK3CA gene are common events in penile squamous cell carcinoma of Italian and Ugandan patients

Abstract: Penile carcinoma develops either through human papillomavirus (HPV) related or unrelated carcinogenic pathways. Genetic alterations and nucleotide changes in coding regions (ie, TP53, CDKN2A, PIK3CA and NOTCH1) are main cancer driver events either in HPV positive or in HPV negative tumours. We investigated the presence of hotspot nucleotide mutations in TERT promoter (TERTp) and PIK3CA exon 9 and their relationship with HPV status in 69 penile cancer cases from Italian and Ugandan patients. Genetic variations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…We and others have shown that TERT promoter mutations, causing hyperactivation of telomerase, are highly frequent in HPV-related cancers and HCV-related hepatocellular carcinoma [ 28 , 31 , 32 , 135 , 171 ]. In particular, all TERT promoter mutations are G>A transitions, which generate novel E-twenty-six binding sites, affect chromatin looping, interfere with the interaction of telomeres with the TERT loci as well as destabilizing the DNA secondary structures and G-quadruplexes formed within the TERT promoter [ 171 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We and others have shown that TERT promoter mutations, causing hyperactivation of telomerase, are highly frequent in HPV-related cancers and HCV-related hepatocellular carcinoma [ 28 , 31 , 32 , 135 , 171 ]. In particular, all TERT promoter mutations are G>A transitions, which generate novel E-twenty-six binding sites, affect chromatin looping, interfere with the interaction of telomeres with the TERT loci as well as destabilizing the DNA secondary structures and G-quadruplexes formed within the TERT promoter [ 171 ].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, single nucleotide mutations in the proximal promoter of the TERT gene, particularly at positions-124A and -146A upstream of the ATG start site, have been shown to generate de novo consensus binding motifs (GGAA) for the E-Twenty-Six family transcription factors causing the aberrant expression of telomerase [ 23 , 25 , 26 , 27 ]. These mutations are highly frequent in a vast majority of cancers including glioblastoma (80–90%), melanoma (70%), basal cell carcinoma (70%), hepatocellular carcinoma (60%), bladder cancers (60%), penile carcinoma (53%), conjunctival carcinoma (46%) and oral cancer (above 30%) [ 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Tert Expression and Telomerase Activitiesmentioning
confidence: 99%
“…We and others have shown that TERT promoter mutations, causing hyperactivation of telomerase, are highly frequent in HPV-related cancers and HCV-related hepatocellular carcinoma [28,31,32,125,156]. Particularly, all TERT promoter mutations are G>A transitions, which generate novel E-twenty-six binding sites, affect chromatin looping, interfere with the interaction of telomeres with the TERT loci as well as destabilize the DNA secondary structures and G-quadruplexes formed within the TERT promoter [156].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, single nucleotide mutations in the proximal promoter of TERT gene, particularly at positions -124A and -146A upstream the ATG start site, have been shown to generate de novo consensus binding motifs (GGAA) for E-Twenty-Six family transcription factors causing the aberrant expression of telomerase [23,[25][26][27]. These mutations are highly frequent in a vast majority of cancers including glioblastoma (80-90%), melanoma (70%), basal cell carcinoma (70%), hepatocellular carcinoma (60%), bladder cancers (60%), penile carcinoma (53%), conjunctival carcinoma (46%) and oral cancer (above 30%), [28][29][30][31][32][33].…”
Section: Tert Expression and Telomerase Activitiesmentioning
confidence: 99%
“…Rb1, CDKN2A and TP53 mutations are known to be involved in penile cancer development [ 32 34 ]. Genetic alterations and nucleotide changes in coding regions like TP53 and CDKN2A have been described as main cancer driver events, both in HPV-positive and in HPV-negative tumors [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%